A 3D analysis of the metal distribution in the compact group of galaxies HCG 31. Issue Volume 10:Issue S309(2014) (9th February 2015) - Torres-Flores, Sergio; Mendes de Oliveira, Claudia; Alfaro-Cuello, Mayte; Carrasco, Eleazar Rodrigo; de Mello, Duilia; Amram, Philippe
Abstract: We present new Gemini/GMOS integral field unit observations of the central region of the merging compact group of galaxies HCG 31. Using this data set, we derive the oxygen abundances for the merging galaxies HCG 31A and HCG 31C. We found a smooth metallicity gradient between the nuclei of these galaxies, suggesting a mixing of metals between these objects. These results are confirmed by high-resolution Fabry-Perot data, from which we infer that gas is flowing between HCG 31A and HCG 31C.